Reforma de la ley de desarrollo agrario incorporando un articulo para prevenir las invaciones de los predios rústicos en el Ecuador - Cholota Cholota, Luis Alfonso (2014)
The land had, has and will always have a strong bond to people and groups throughout society. The dispute for land and the right to use, the impact of relations between human beings and the earth, are characteristic features that are repeated throughout human history. The Constitution of the Republic of Ecuador in its Article 321 in relation to types of property states "The State recognizes and guarantees the right to property forms public, private, community, state, association, cooperative, mixed and to be meet their social and environmental. " Agrarian Development Act, in article 28 provides "The State guarantees the integrity of farm holdings. In case of invasions and land grabs, the provisions of the Constitution and other laws." In Ecuador, people invade land is ill-advised individuals or the state, creating intractable conflicts. The Ecuadorian legislature has not been diligent in finding solutions to this problem and create clear laws guaranteeing private property. In this legal research conducted a detailed study of theoretical and legal framework regarding property and rural land invasions of Ecuador, to provide a legal proposal that avoids these problems continue to occur.